2017
DOI: 10.18632/oncotarget.19445
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol promotes MICA/B expression and natural killer cell lysis of breast cancer cells by suppressing c-Myc/miR-17 pathway

Abstract: Major histocompatibility complex class I chain-related proteins A and B (MICA and MICB) are important ligands for recognition of tumor cells by immune effector cells. Here, we report that resveratrol upregulated the protein and mRNA expression of MICA and MICB in breast cancer cells, which in turn promoted breast cancer cell lysis by natural killer (NK) cells in vitro and in vivo. Antibodies against NK group 2 member D blocked this effect. The 3′-untranslated regions of MICA and MICB were found to be direct bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 53 publications
2
49
0
Order By: Relevance
“…Conversely, resveratrol upregulates MICA/MICB mRNA and protein expression levels in breast cancer cells, which, in turn, enhances breast cancer cytolysis by NK cells in vitro and in vivo. In that study, the authors also demonstrated that resveratrol downregulates c‐Myc–dependent miR‐17 expression, which, if untreated, represses MICA/MICB expression . In agreement with these results, it has been reported that resveratrol prompts cytokine‐induced, killer cell‐mediated cytolysis of promyeloblastic leukemia KG‐1a cells through increased expression of NKG2D ligands and activation of the TNF‐related apoptosis‐inducing ligand (TRAIL) pathway .…”
Section: Natural Compounds Possessing Epigenetic Properties That Stimsupporting
confidence: 71%
See 1 more Smart Citation
“…Conversely, resveratrol upregulates MICA/MICB mRNA and protein expression levels in breast cancer cells, which, in turn, enhances breast cancer cytolysis by NK cells in vitro and in vivo. In that study, the authors also demonstrated that resveratrol downregulates c‐Myc–dependent miR‐17 expression, which, if untreated, represses MICA/MICB expression . In agreement with these results, it has been reported that resveratrol prompts cytokine‐induced, killer cell‐mediated cytolysis of promyeloblastic leukemia KG‐1a cells through increased expression of NKG2D ligands and activation of the TNF‐related apoptosis‐inducing ligand (TRAIL) pathway .…”
Section: Natural Compounds Possessing Epigenetic Properties That Stimsupporting
confidence: 71%
“…In that study, the authors also demonstrated that resveratrol downregulates c-Myc-dependent miR-17 expression, which, if untreated, represses MICA/MICB expression. 91 In agreement with these results, it has been reported that resveratrol prompts cytokine-induced, killer cellmediated cytolysis of promyeloblastic leukemia KG-1a cells through increased expression of NKG2D ligands and activation of the TNF-related apoptosis-inducing ligand (TRAIL) pathway. 92 Accumulating evidence also suggests that resveratrol can be a good candidate for combination immunotherapy.…”
Section: Curcuminsupporting
confidence: 66%
“…Curcumin induces apoptosis in multiple myeloma via modulation of the EZH2‐miR‐101 regulatory feedback loop . Resveratrol enhances the expression of major histocompatibility complex class I chain‐related proteins A and B via inhibition of the c‐Myc/miR‐17 pathway in breast cancer cells . Berberine also regulates the expression of microRNAs in various cancers.…”
Section: Epigenetic Basis Of Tcmmentioning
confidence: 99%
“…190 Resveratrol enhances the expression of major histocompatibility complex class I chain-related proteins A and B via inhibition of the c-Myc/miR-17 pathway in breast cancer cells. 199 Berberine also regulates the expression of microRNAs in various cancers. In SGC-7901 cells treated with berberine, 347 microRNAs were found to be upregulated and 93 downregulated following miRNA sequencing.…”
Section: Noncoding Rna Regulationmentioning
confidence: 99%
“…Several cancers have been found to overexpress miRNAs that can bind the 3'UTR of MICA and MICB genes. Specifically, miR‐17, miR‐20a, and miR‐93 are components of the miR‐17‐92 cluster and all bind to the same regions in both MICA and MICB genes. While this site is conserved among MICB 3'UTR sequences, these miRNAs bind positions 11640‐11662 encompassing the A/G dimorphism at position 11653 of the MICA gene.…”
Section: Discussionmentioning
confidence: 99%